In Silico Exploration of Natural Antioxidant Candidates: Capsaicin Compounds from Cayenne Pepper Leaves (Capsicum frutescens L.) as Potential Inhibitors of the COX-2 Enzyme (PDB ID:5IKQ) - Esti Febri Fatwami Esti Febri Fatwami; Dian Islamiyati; Ryan Syahputra (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Exposure to free radicals caused by oxidative stress is a major factor in cellular damage and contributes to the development of degenerative diseases, highlighting the need for safe and effective natural antioxidants. Oxidative stress is triggered by excessive production of Reactive Oxygen Species (ROS), in which cyclooxygenase-2 (COX-2) plays a key enzymatic role in ROS formation. Cayenne pepper leaves (Capsicum frutescens L.) are known to possess antioxidant potential, with capsaicin identified as an important secondary metabolite. The antioxidant potential of capsaicin was evaluated using an in-silico approach by analyzing its binding affinity and molecular interactions with the COX-2 enzyme. This research aimed to assess capsaicin from cayenne pepper leaves as a potential natural antioxidant candidate through in silico interaction analysis with COX-2. Molecular docking was performed using AutoDock software to determine binding affinity values and optimal ligand conformations at the active site of COX-2. Interaction visualization and amino acid residue analysis were conducted using Discovery Studio Visualizer. The docking results were compared with the native ligand based on binding affinity and inhibition constant (Ki) values to evaluate inhibitory potential. Capsaicin exhibited a binding affinity of −7.41 kcal/mol and a Ki value of 3.73 µM, indicating stable interaction with COX-2. Although its binding affinity was lower than that of the native ligand, capsaicin demonstrated sufficient interaction strength to be classified as a potential natural COX-2 inhibitor. These findings suggest that capsaicin derived from cayenne pepper leaves may possess natural antioxidant activity based on in silico analysis.